Changing Infliximab Prescription Patterns in Inflammatory Bowel Disease: A Population-Based Cohort Study, 1999–2014. Issue 2 (18th January 2018) - Larsen, Lone; Drewes, Asbjørn Mohr; Broberg, Marie Christine Hede; Fallingborg, Jan; Jacobsen, Bent Ascanius; Jensen, Thomas Bo; Jess, Tine
Abstract: Background: Long-term data on real life use of infliximab (IFX) for inflammatory bowel disease (IBD) are lacking. We studied prescription patterns during the first 16 years following marketing authorization. Methods: In a population-based cohort from the North Denmark Region, all IBD patients exposed to IFX during 1999 to 2014 were identified. Results: A total of 623 patients (210 with ulcerative colitis [UC] and 413 with Crohn's disease [CD]) were exposed to IFX. In patients with UC, age at first exposure decreased by 10 months per calendar year ( P < 0.05) during the study period. In patients with CD, disease duration at time of first IFX exposure decreased by 7 months per calendar year ( P < 0.001). From 2005–2009 to 2010–2014, the proportion of IFX-exposed patients with pancolitis (40% vs 24%, P = 0.04) and the proportion of patients with extensive CD ( P = 0.002) decreased. The mean time to discontinuation of IFX remained stable in patients with CD during the study period (2.5–3.0 years) and increased from 0.34 years (2005–2009) to 1.11 years (2010–2015) in patients with UC ( P = 0.04). Conclusion: During the first 16 years postmarketing, age at first exposure to IFX decreased in patients with UC, whereas disease duration at time of first exposure decreased in patients with CD. Also, a significant change toward less extensive disease in both UC and CD patients exposed to IFX was observed. Treatment duration in patients with UC increased during the study period, but did not reach the more constant and longer duration of treatment observed in patients with CD.